Structural assessment of building Elementary School 28 Air Tawar Timur Padang - Prima Yane Putri; Candra Candra (invotek, 2022)
Abstract ˗˗The State Elementary School 28 Air Tawar Timur Padang is an Inpres School which was built in 1982. The current condition of the school building is damaged, such as cracks, loose concrete (spalling), deflection and shaking floors. This study aims to provide recommendations for repair or maintenance of the school building. The assessment method used in this study is the Non Destructive Test (NDT) method. Testing the compressive strength of concrete using a Schmidt Rebound Hammer. To see the amount of reinforcing steel, diameter of reinforcing steel and dimensions of structural elements using a Rebar Locator, Caliper, and a meter. Testing the building geometry and deflection floor plates using Total Station and Laser Measurement. The building structure was analyzed using the SAP2000 program. The results of the concrete compressive strength test (fc ') are on average 20.40 MPa on the column, 22.23 MPa on the beam, and 23.43 MPa on the floor plate. The results of visual observations of the building are categorized as severely damaged with the proportion of damage above 20%. Where the proportion level of column damage is 32%, beams 20.35%, and the floor court is 65%. The results of the building structure evaluation show that all elements are categorized as unsafe except Beams 3, Beams 4, and Column 2. The maximum deflection of the floor as high as 73 mm exceeds the allowable permit, which is 18.9 mm. The recommendation for repair of the school is building renovation.